(untitled) (Latakia University Journal -Medical Sciences Series, 2023)
The science of massaging is tought in the faculty physical education, containing both the practical and theortical aspects, which provides the students with profeceional medical culture. The senior students will learn the basics of massage moves and apply it in different suiting conditions. This study aims to put the spotlight on the ability to use the terms of the curriculum and its teaching methods according to quality, viliability and NARS standards. In which 38 students have undergone survey to support the research the results were convenient to the content of the curriculum, teaching methods and compatible with the scientifical needs of students.